Bakha’s Identity Dilemma in Mulk Raj Anand’s Untouchable: An Exploration of Dalit Psychology - Sadia Afrin; Sheikh Md. Muniruzzaman (Asiatic: IIUM Journal of English Language and Literature, 2022)
The Indian English-language writer Mulk Raj Anand depicts psychological crises of the subaltern through the character of Bakha in his masterpiece, Untouchable (1935). He attempts to portray the psychological vulnerability of the outcastes of society through the depiction of the Dalit community. This study explores the true nature of Dalit psychology through discussing Bakha’s equivocal status as a result of social discrimination and racial binary. It analyses the multifaceted dominations that the so-called elite class imposes on the subordinates who have taken these appalling social conditions for granted. Although not drawn from Dalit literature, a theoretical and critical reading reveals that William Shakespeare’s Shylock, Othello, and Caliban, Emily Bronte’s Heathcliff, Khaled Hosseini’s Ali, Hassan, and Sohrab bear significant resemblance to Bakha in terms of identity confusion. Using analytical methods drawn from post- colonialism and psychoanalysis, this article seeks to discuss Bakha’s psyche as a representation of the plight of the oppressed and Dalit people.